Depression of Non-Neuronal Cholinergic System May Play a Role in Co-Occurrence of Subjective Daytime Sleepiness and Hypertension in Patients with Obstructive Sleep Apnea Syndrome - Meng Z; Sun B; Chen W; Zhang X; Huang M; Xu J (Nature and Science of Sleep, 2021)
Zili Meng,1,* Bing Sun,1,* Wei Chen,1,* Xilong Zhang,2 Mao Huang,2 Jing Xu1 1Department of Respiratory and Critical Care Medicine, The Affiliated Huaian No. 1 People’s Hospital of Nanjing Medical University, Huaian, Jiangsu, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital with Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing XuDepartment of Respiratory and Critical Care Medicine, The Affiliated Huaian No. 1 People’s Hospital of Nanjing Medical University, 6 Beijing Road West, Huaian, Jiangsu, 223300, People’s Republic of ChinaTel +86-13912080023Fax +86-517 83724440Email xj680390@126.comPurpose: Simultaneous occurrence of hypertension and excessive daytime sleepiness (EDS) is very common in obstructive sleep apnea syndrome (OSAS), although no study has specifically addressed this issue. The present study explored the risk factors for co-occurrence of OSAS-related EDS and hypertension.Patients and Methods: A total of 161 OSAS patients were studied after undergoing an eight-hour in-laboratory polysomnography for one night. The OSAS severity assessment depends on the number of breathing disturbances per hour of sleep. EDS was defined using the Epworth Sleepiness Scale (ESS) scores of ≥ 13. Hypertension was defined according to direct cuff blood pressure (BP) measurements. Beat-to-beat R-R interval data were incorporated in polysomnography for heart rate variability analysis. The low-frequency/high-frequency band ratio was used to reflect sympathovagal balance. The study participants were divided into four groups based on the presence of EDS and/or hypertension: EDS with hypertension (n = 53), EDS without hypertension (n = 27), no EDS with hypertension (n = 38), and no EDS or hypertension (n = 43). Clinical, polysomnographic and heart rate data were compared and studied among the four groups. Plasma acetylcholine (ACh) levels were assessed to explore the effects of the non-neuronal cholinergic system and the co-occurrence of EDS and hypertension.Results: Patients with EDS and hypertension had more severe OSAS severity indices compared to control patients. Increased cardiac sympathovagal imbalance and nocturnal hypoxemia regulated the presence of EDS and hypertension. Further plasma biomarker analysis revealed that both ESS scores and BP levels were associated with significantly elevated plasma norepinephrine, interleukin-6 and superoxide dismutase levels and significantly decreased ACh levels. Logistic regression analyses showed that ACh was the only factor significantly associated with co-occurrence of EDS and hypertension after controlling for confounders using odds ratio of 0.932, with a 95% confidence interval of 0.868 to 1.000 (P = 0.049).Conclusion: The results suggested that OSAS coupled with both EDS and hypertension is a more severe phenotype of the respiratory disorder. The presence of EDS and hypertension was accompanied by sympathovagal imbalance, and co-occurrence of these two conditions may be related to decreased plasma ACh levels.Keywords: acetylcholine, subjective excessive daytime sleepiness, hypertension, obstructive sleep apnea